Epigenetic Regulation in Hydra: Conserved and Divergent Roles - Pillai, Anirudh; Gungi, Akhila; Reddy, Puli Chandramouli; Galande, Sanjeev (Frontiers in Cell and Developmental Biology, 2021)
Transitions in gene regulatory processes responsible for the emergence of specialized cell types and spatiotemporal regulation of developmental signaling prior to the divergence of Cnidaria and Bilateria are poorly understood. As a sister group of Bilateria, the phylum Cnidaria can provide significant insights into these processes. Among the cnidarians, hydrae have been studied for >250 years to comprehend the mechanisms underlying their unique immortality and robust regenerative capacity. Studies on Hydra spp. and other pre-bilaterians alike have advanced our understanding of the evolutionary underpinnings governing eumetazoan tissue development, homeostasis, and regeneration. In addition to its regenerative potential, Hydra exhibits continuously active axial patterning due to its peculiar tissue dynamics. These distinctive physiological processes necessitate large scale gene expression changes that are governed by the multitude of epigenetic mechanisms operating in cells. This review highlights the contemporary knowledge of epigenetic regulation in Hydra with contemporary studies from other members of Cnidaria, as well as the interplay between regulatory mechanisms wherever demonstrated. The studies covered in the scope of this review reveal both ancestral and divergent roles played by conserved epigenetic mechanisms with emphasis on transcriptional regulation. Additionally, single-cell transcriptomics data was mined to predict the physiological relevance of putative gene regulatory components, which is in agreement with published findings and yielded insights into the possible functions of the gene regulatory mechanisms that are yet to be deciphered in Hydra, such as DNA methylation. Finally, we delineate potentially rewarding epigenetics research avenues that can further leverage the unique biology of Hydra.